A scoping review of research on digital game-based language learning. (November 2018) - Hung, Hsiu-Ting; Yang, Jie Chi; Hwang, Gwo-Jen; Chu, Hui-Chun; Wang, Chun-Chieh
Abstract: The continuing attention to the educational value of digital games highlights the need for more focused literature reviews in order to identify critical gaps and opportunities in domain-specific areas. The current study thus set out to provide a scoping overview of empirical evidence on the use and impacts of digital games in language education from 2007 to 2016, as a means to advance the emerging research on digital game-based language learning (DGBLL). A total of 50 selected studies were systematically analyzed, revealing the following findings: (1) Most of the selected DGBLL studies adopted mixed methods to examine the educational use of digital games; (2) Immersive games, notably massively multiplayer online role-playing games, were the most common genre in the current DGBLL literature; (3) Most of the games for language learning were custom-built by DGBLL researchers; (4) Personal computers were the most common platforms for playing games to support language learning; (5) Most of the DGBLL studies adopted games to facilitate the learning of English as a second or foreign language; (6) Most of the research on DGBLL investigated learners with mixed levels of language proficiency; (7) University students were the most frequently selected samples in the existing DGBLL literature; and (8) The majority of DGBLL studies featured positive outcomes in regard to student learning, with the most frequently reported ones being related to affective or psychological states, closely followed by language acquisition. Taken as a whole, these findings reflect the diverse nature of this field and suggest the overall feasibility of using digital games for promoting the language and literacy learning of both native and non-native speakers in various aspects. Several promising but under-researched areas were also identified in this review, along with discussions on their implications for future investigations. Highlights: A review of empirical studies on digital games for language learning was conducted. A variety of game genres were identified, with immersive games being most popular. Most of the studies adopted games to facilitate the teaching and learning of English. The reviewed studies featured positive student learning outcomes in various aspects. Several promising but under-researched areas were discussed with suggestions.